THE HUYULA TRADITION AMONG THE COMMUNITY OF MANANGGU VILLAGE, MANANGGU DISTRICT, BOALEMO REGENCY, GORONTALO PROVINCE - Greviana Rubai; Tonny Iskandar Mondong; Naufal Raffi Arrazaq; Irvan Tasnur (CV. Fahr Publishing, 2026)
This study aims to examine the existence of the huyula (mutual cooperation) tradition in the lives of the people of Mananggu Village, Mananggu District, Boalemo Regency, Gorontalo Province. The research used a qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that huyula is still practiced, especially in social events such as weddings and funerals, reflecting strong community solidarity and mutual care. The core values embedded in this tradition include sincerity, cooperation, unity, and selfless service. However, the practice of huyula is gradually declining in agricultural and other productive sectors due to socio-economic changes and the more individualistic mindset of younger generations. Nevertheless, the community still possesses the awareness and skills needed to carry out this tradition. The role of cultural leaders, village institutions, and educational efforts is essential to revitalize and preserve huyula as a marker of local cultural identity. This tradition remains relevant as a model of community collaboration that strengthens social cohesion amidst modernization.